miRNA-7062-5p Promoting Bone Resorption After Bone Metastasis of Colorectal Cancer Through Inhibiting GPR65 - Chen, Liang; Wang, Yu; Lu, Xingchen; Zhang, Lili; Wang, Ziming (Frontiers in Cell and Developmental Biology, 2021)
Bone metastasis is positively associated with a poor prognosis in patients with colorectal cancer (CRC). CRC always leads to osteolytic change, which is regulated by aberrant activation of osteoclasts. MicroRNAs are remarkedly involved in metastasis of CRC; however, their role in bone metastasis of CRC is still unclear. The aim of this study is to find key microRNAs that are critical to bone resorption in bone metastasis of CRC. In this study, bone metastasis model was established through intratibially injecting CT-26 cells or MC-38 cells. Tartrate-resistant acid phosphatase (TRAP) staining was performed to explore the osteoclastogenesis of primary early osteoclast precursors (OCPs) after stimulation by CT-26 conditioned medium (CM). Then, microarray assay was performed to find differentially expressed miRNAs and mRNAs. The target gene of miRNA was confirmed by dual-luciferase analysis. The effect of miRNA, its target gene on osteoclastogenesis, and involved pathways were explored by Western blot, immunofluorescence analysis, and TRAP staining. Finally, the effect of miRNA on bone resorption in vivo was observed. miRNA-7062-5p was upregulated in early OCPs cultured in CT-26 CM or MC-38 CM. GPR65 was proven to be the target gene of miRNA-7062-5p. Overexpression of GPR65 can rescue the osteoclastogenesis caused by miRNA-7062-5p through activation of AMPK pathway. Local injection of miRNA-7062-5p inhibitors efficiently improved the bone resorption. Our study found the role of miRNA-7062-5p in regulating osteoclast formation, and our findings provided a potential therapeutic target in treatment of bone metastasis of CRC.